2004
DOI: 10.1097/01.ico.0000116526.57227.82
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and Conjunctival Changes Caused by Commonly Used Glaucoma Medications

Abstract: Although the adverse effects of glaucoma medications on the ocular surface are likely multifactorial, 1-month treatment with glaucoma medications containing higher levels of benzalkonium chloride (BAK) resulted in greater corneal damage and conjunctival cell infiltration than medications preserved with Purite or with lower levels of BAK. Using glaucoma medications with alternative preservatives or low levels of BAK may help preserve ocular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
149
1
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(172 citation statements)
references
References 16 publications
9
149
1
13
Order By: Relevance
“…These corneal epithelial images are consistent with previously published reports. [4][5][6][7]18,34 The results of the NRCE cell viability assay after exposure to travoprost additives with or without BAC were similar to the results of the TER measurements.…”
Section: Discussionsupporting
confidence: 52%
“…These corneal epithelial images are consistent with previously published reports. [4][5][6][7]18,34 The results of the NRCE cell viability assay after exposure to travoprost additives with or without BAC were similar to the results of the TER measurements.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, a recent paper demonstrated that drugs containing 0.005% BAC cause only minimal damage to the ocular surface even when dosed chronically. 38 Furthermore, the new product will also be the first steroid/antibiotic combination available in a preservative-free formulation; efficacy and safety of the latter is comparable to that of the preserved formulation reported herein (Russo S et al, unpublished data).…”
Section: Discussionsupporting
confidence: 53%
“…Multiple studies have delineated the deleterious effects of BAK on conjunctival epithelium, corneal epithelium and corneal stroma. 4,[9][10][11][12][13][14][15][16][17][18][19][20] The microscopic changes seen in patients taking BAK include an increase of pro-infl ammatory cytokines, lymphocyte infi ltration, fi broblast proliferation, corneal microvilli loss and goblet cell loss in the conjunctival epithelium. In addition, these ocular surface changes may decrease the success rate of glaucoma surgery.…”
Section: Discussionmentioning
confidence: 99%